Motivations for Specializing in English at the Graduate Level of University Education: A Narrative Inquiry - Atreya, Hari Raj (English Language Teaching Perspectives, 2025)
The study aimed to explore the learners’ motivational factors for specializing in English in the university education system in Nepal. This study employed a qualitative research approach, specifically adopting the narrative inquiry design. The participants consisted of five second-year Bachelor of Education students majoring in English at the university level. They were selected through purposive sampling to ensure relevance to the research focus. Data were collected using a semi-structured interview guideline. The collected data were ethically handled, systematically coded, and analyzed. Following the coding process, themes were developed and discussed thematically to derive meaningful insights. The study’s findings showed that learners are motivated by competitive events and functions, interpersonal and self-motivation, job and finance, results of previous examinations, and study and university-level employment abroad. They were motivated from the early age of schooling to the immediate past education portfolio, grade XII. Motivations for specializing in English had multiple factors depending on the contents and contexts. Intrinsic motivations of the learners were explored in the study, but further researchers need to dig out probable supporting motivational aspects, both intrinsic and extrinsic, to enhance the specialization in the English language. The findings of the study demand further studies in the area of motivations for the learners.